Chemical vapour deposition of chromium-doped tungsten disulphide thin films on glass and steel substrates from molecular precursors. Issue 35 (24th August 2018) - Murtaza, Ghulam; Venkateswaran, Sai P.; Thomas, Andrew G.; O'Brien, Paul; Lewis, David J.
Abstract : Polycrystalline thin films of chromium doped tungsten disulphide (WS2 ) have been deposited onto glass and steel substrates by Aerosol-Assisted Chemical Vapour Deposition (AACVD) at 450 °C. Abstract : Polycrystalline thin films of chromium doped tungsten disulphide (WS2 ) have been deposited onto glass and steel substrates by Aerosol-Assisted Chemical Vapour Deposition (AACVD) using bis(diethyldithiocarbamato)disulfidothioxo tungsten(vi ) (WS3 L2 ) and tris(diethyldithiocarbamato) chromium(iii ) [Cr(S2 CNEt2 )3 ] (CrL3 ) complexes as precursors in different molar ratios at 450 °C. The deposited films were characterised by p-XRD, SEM, and EDX and Raman spectroscopies. Chromium doping of up to 15 mol% was achieved in WS2 thin films.